2009
DOI: 10.1111/j.1742-4658.2009.07014.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐23b mediates urokinase and c‐met downmodulation and a decreased migration of human hepatocellular carcinoma cells

Abstract: Urokinase‐type plasminogen activator (uPA) and c‐met play a major role in cancer invasion and metastasis. Evidence has suggested that uPA and c‐met overexpression may be coordinated in human hepatocellular carcinoma (HCC). In the present study, to understand whether the expression of these genes might be coregulated by specific microRNAs (miRs) in human cells, we predicted that Homo sapiens microRNA‐23b could recognize two sites in the 3′‐UTR of uPA and four sites in the c‐met 3′‐UTR by the algorithm pictar. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 42 publications
9
115
0
Order By: Relevance
“…2). We showed that AM23b reversed the EC growth arrest under PS; this is in concert with the finding that miR-23b overexpression decreases hepatocelluar carcinoma cell proliferation (39). Although both AM23b and AM27b can regulate E2F1 expression, only AM23b significantly reduced the PS-induced Rb hypophosphorylation and cell cycle arrest.…”
Section: Discussionsupporting
confidence: 85%
“…2). We showed that AM23b reversed the EC growth arrest under PS; this is in concert with the finding that miR-23b overexpression decreases hepatocelluar carcinoma cell proliferation (39). Although both AM23b and AM27b can regulate E2F1 expression, only AM23b significantly reduced the PS-induced Rb hypophosphorylation and cell cycle arrest.…”
Section: Discussionsupporting
confidence: 85%
“…Although a few studies recently demonstrated that miR-23b is involved in invasion and metastasis, the molecular mechanism remains to be elucidated 30,31 . Th e data reported here demonstrated that miR-23b, which is downregulated in human colon cancer samples, could potently repress cancer cell migration, invasion, growth and angiogenesis both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of c-Met through aberrant hepatocyte growth factor paracrine stimulation contributes to tumor invasion and metastasis, with overexpression of c-Met associated with bladder cancer progression and poor prognosis (Cheng et al, 2002;2005). The microRNAs miR-23b, miR-34a and miR-198 have been reported to inhibit migration and invasion through down-regulation of c-Met expression in human hepatocellular carcinoma cells (Li et al, 2009;Salvi et al, 2009;Tan et al, 2011). Another report indicates that the anti-metastatic miR-340 inhibits breast cancer metastasis by targeting c-Met (Wu et al, 2011).…”
Section: A B C Dmentioning
confidence: 99%